Accelerated discovery of defect tolerant organo-halide perovskites - YAVUZ, İLHAN (My University, 2022)
© 2022 The Royal Society of Chemistry.One of the most effective ways to increase power conversion efficiency and maintain stability in hybrid organic-inorganic perovskite (HOIP) semiconductor materials is to avoid defect formation. A rapid screening of defects and trap-states of many HOIP candidate materials is required. For this, we have implemented an \"accelerated\" material discovery strategy to predict the electronic structures and defects of HOIP-candidate materials by using artificial intelligence and density functional theory. We rationalize material classification and structure-property relationships. With this strategy, we were able to propose previously undiscovered HOIP materials that are defect-tolerant and active candidates for perovskite solar cells. We found that HOIPs are more sensitive to halide interstitial defects rather than halide vacancy defects. Semiconductor HOIPs typically form relatively unstable/shallow halide vacancy defects and stable/deep halide interstitial defects.
Keywords: Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Kimya; Fizik Bilimleri; Malzeme Kimyası; General Chemistry; Physical Sciences; Materials Chemistry